Public Perception and Awareness of the Sustainable Development Goals (SDGs) in Indonesia: A National Survey - Yuliani Sekriptini, Ayu; Haji Omar, Rina; Soares, Fatima (Yayasan Adra Karima Hubbi, 2025)
Background. Public understanding and awareness of the Sustainable Development Goals (SDGs) are essential for ensuring effective national implementation, promoting community participation, and strengthening shared responsibility for sustainable development. Indonesia, as one of the earliest adopters of the SDGs, continues to integrate the goals into national policies, local governance, and development programs. Despite these efforts, limited empirical research has examined the extent of public awareness, perceived relevance, and engagement with the SDGs across the Indonesian population. A national survey is therefore needed to assess public perception and identify gaps in knowledge that may hinder broader societal support for sustainability initiatives. Purpose. This study aims to evaluate the level of public awareness, understanding, and attitudes toward the SDGs in Indonesia by analyzing demographic influences, information sources, and perceived national priorities. The research also seeks to identify barriers to SDG engagement and provide recommendations for enhancing public participation in sustainability initiatives. Method. A nationwide quantitative survey was conducted involving 1,462 respondents selected through stratified random sampling to represent Indonesia’s major demographic groups. Data were collected through structured online and offline questionnaires measuring awareness levels, perceived importance of SDGs, and individual behavioral commitments. Descriptive statistics, cross-tabulations, and regression analysis were used to examine patterns and predictors of SDG awareness. Results. Findings reveal that overall awareness of the SDGs is moderate, with substantial variation across age, education level, and urban–rural residence. Respondents identify climate action, poverty reduction, and quality education as the most relevant SDGs for Indonesia, while awareness of goals related to marine ecosystems and responsible consumption remains low. Regression results indicate that education level, media exposure, and civic engagement significantly predict SDG awareness. Conclusion. The study concludes that strengthening SDG literacy through public campaigns, educational integration, and community-based programs is essential for advancing sustainable development efforts in Indonesia.